Improving profitability and livelihood security of marginal farmers in Kandi area of Jammu - GUPTA, MEENAKSHI; KOUR, SARABDEEP; BHARAT, RAJEEV (Journal of Soil and Water Conservation, 2023)
An attempt was made to improving profitability and livelihood security of marginal farmers in Kandi area of Jammu region. On farm trial was conducted from kharif 2015 to rabi 2017-18 on mixed cropping systems in the kandi area. To mitigate the risk and uncertainty of arable cropping various agricultural enterprises were integrated so that farmer gets higher yield and regular income. Multipurpose trees (MPTs) were also planted on the borders of the field. Traditionally, intercropping in fruit orchard was practiced under irrigated situation, but with the harvesting of rainwater it was possible to utilize the land unit efficiently by cultivating field crops, which helped to increase both productivity and profitability. The study indicated enhanced growth of citrus fruits along with intercrops. The increase in fruit yield after interventions was to the tune of 36% after three years of study. Among all the systems, fruit production was maximum (4920 q/ha) during rabi 2017-18, with benefit: cost ratio showed that citrus trees gave a higher value of 6.04. Maize-Wheat-Fruit-Goat was highly profitable system which recorded net returns of Rs. 1,85,628/- and system profitability of Rs.508.5/ha/day which was followed by Bajra- Wheat-Fruit-Goat system. Maximum employment generation (146 days) was seen in the Mustard-Wheat- Fruit-Goat system followed by Bajra-Wheat-Fruit-Goat (125 days). The multipurpose trees on the border areas of the farm helped to save land and increase cropping area. The green leaves obtained from loppings were used as fodder for cattle, fuel wood for house hold use besides getting additional income from sale of wood.